2001
DOI: 10.1161/hh2401.101084
|View full text |Cite
|
Sign up to set email alerts
|

Integrin and Growth Factor Receptor Crosstalk

Abstract: Abstract-Crosstalk between integrins and growth factor receptors are an important signaling mechanism to provide specificity during normal development and pathological processes in vascular biology. Evidence from several model systems demonstrates the physiological importance of the coordination of signals from growth factors and the extracellular matrix to support cell proliferation, migration, and invasion in vivo. Several examples of crosstalk between these two important classes of receptors indicate that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
298
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(305 citation statements)
references
References 93 publications
6
298
0
1
Order By: Relevance
“…A: CAT activity increases as HSC activation progresses. CAT was extracted at days 3,5,7,8,16,23, and 28 of the primary culture by harvesting cells followed by 3 cycles of freezing and thawing. CAT activity was determined by incorporation of [ 3 H]acetate from acetyl CoA into chloramphenicol as described in MATERIALS AND METHODS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A: CAT activity increases as HSC activation progresses. CAT was extracted at days 3,5,7,8,16,23, and 28 of the primary culture by harvesting cells followed by 3 cycles of freezing and thawing. CAT activity was determined by incorporation of [ 3 H]acetate from acetyl CoA into chloramphenicol as described in MATERIALS AND METHODS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DDR2, which binds type I collagen, is upregulated in activated HSC and its stimulation contributes to proliferation and invasiveness of activated HSC (32). In addition, type I collagen-and laminin-binding integrins have been reported to exist on HSC membrane and to mediate HSC proliferation and apoptosis (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of different subunits originates distinct integrins that mediate cell adhesion to a variety of adhesive proteins of the ECM [133]. Integrins regulates also the response of endothelial cells to soluble growth factors, including FGF2 [134], but the molecular mechanism(s) of this regulation are not fully elucidated. a v b 3 integrin is expressed on endothelial cells where it plays a central role in neovascularization.…”
Section: Integrin Receptorsmentioning
confidence: 99%
“…Angiogenesis occurs in physiological (embryology, ovulation, wound healing) and in pathological situations (neoplasia, diabetic retinopathy, rheumatoid arthritis) [2]. The process is regulated by a balance between pro-and anti-angiogenic molecules, emanating from endothelial, stromal and epithelial cells [3], by comprising growth factors [4], proteinases [5] and their respective inhibitors [6], extracellular matrix molecules [7], and also by cell-cell and cell-substratum adhesion molecules [8].…”
Section: Introductionmentioning
confidence: 99%